Mediation of volatiles on the intra- and interspecific relationships between Angrus nilaparvatae Pang & Wang and Cyrtorhinus lividipennis (Reuter) - LIU Fang; LOU Yong-gen; CHENG Jia-an (浙江大学学报. 农业与生命科学版, 2002)
Mediation of volatiles in the relationships between Angrus nilaparvatae Pang & Wang and Cyrtorhinus lividipennis (Reuter) were studied using rice variety TN1. The results showed that A. nilaparvatae and C. lividipennis did not distinguish volatiles of rice plants with planthoppers (female adults or nymphs) from those of rice plants with planthoppers and conspecific parasitoid or predator. The parasitoid showed no apparent avoidance to odours from rice plants with planthoppers and the predator, while the predator preferred odours from rice plants with planthoppers and the parasitoid over those from plants with planthoppers.